Substantial Near-Surface Spring Ozone Enhancement due to Stratospheric Intrusion in the Northeastern Qinghai–Tibet Plateau, China - Li, Chaoqun; Ma, Mingchen; Kou, Wenbin; Zeng, Xinran; Cheng, Wenxuan; Wang, Houwen; Zhang, Jiankai; Wang, Wuke; Lin, Weili; Li, Hong; Zhu, Yuanyuan; Yao, Xiaohong; et al. (Frontiers in Environmental Science, 2022)
Stratospheric ozone intrusion plays an important role in affecting the tropospheric ozone concentrations in the troposphere through stratosphere to troposphere transport (STT), nevertheless, there are very limited studies on quantification of the effect. Focusing on a typical event during May 9-12, 2015 when STT occurs over the northeastern Qinghai-Tibet Plateau of China, the observations and reanalysis data indicate that STT is accompanied by high potential vorticity and low specific humidity. To quantify to what extent the STT may elevate the ozone concentrations, an inert tracer is added in the boundary conditions of the Community Multiscale Air Quality (CMAQ), which is driven by Weather Research and Forecasting (WRF) model. The meteorological conditions simulated by WRF nicely reproduce the distributions of PV and water vapor in the upper troposphere. Through the physical processes of diffusion, advection, dry and wet deposition, the ozone tracer concentrations simulated from CMAQ well captures the spatial propagation and evolution of stratospheric ozone intrusion over Qinghai-Tibet Plateau, warranting the confidence in interpreting the simulated results in quantifying the STT. The STT event indicates the near surface ozone enhancement of approximately 10-20 ppbv covering half of Qinghai Province, even spreading to a broader area of eastern China. For the typical remote mountain such as Waliguan, clear ozone enhancement is obtained over the lower level of the troposphere as well. The method used in this study is applicable to other regions as well, which can be applied in the future to detect the STT in a wider spatiotemporal scale and help the policy makers to identify the ozone sources as well as make efficient strategies in the ozone pollution control.